2019
DOI: 10.1029/2018gl081355
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Depletion of the Dissolved Iron Reservoirs in the Sub‐Antarctic Zone of the Southern Atlantic Ocean

Abstract: Seasonal progression of dissolved iron (DFe) concentrations in the upper water column was examined during four occupations in the Atlantic sector of the Southern Ocean. DFe inventories from euphotic and aphotic reservoirs decreased progressively from July to February, while dissolved inorganic nitrogen decreased from July to January with no significant change between January and February. Results suggest that between July and January, DFe loss from both euphotic and aphotic reservoirs was predominantly in supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…Yet it is apparent that iron limitation was less a constraint on NCP during the first warm year, as surface NO 3 − reached exceptional values around 4 μmol/kg in September 2014 ( Figure 4b). Mtshali et al (2019) reported that recycled iron supported seasonally extended primary production in the Southern Ocean; we suggest that this extension reached into the first warm-year growing season in the Gulf of Alaska. Mtshali et al (2019) reported that recycled iron supported seasonally extended primary production in the Southern Ocean; we suggest that this extension reached into the first warm-year growing season in the Gulf of Alaska.…”
Section: Considering the Difference In Net Organic Carbon Production mentioning
confidence: 50%
See 1 more Smart Citation
“…Yet it is apparent that iron limitation was less a constraint on NCP during the first warm year, as surface NO 3 − reached exceptional values around 4 μmol/kg in September 2014 ( Figure 4b). Mtshali et al (2019) reported that recycled iron supported seasonally extended primary production in the Southern Ocean; we suggest that this extension reached into the first warm-year growing season in the Gulf of Alaska. Mtshali et al (2019) reported that recycled iron supported seasonally extended primary production in the Southern Ocean; we suggest that this extension reached into the first warm-year growing season in the Gulf of Alaska.…”
Section: Considering the Difference In Net Organic Carbon Production mentioning
confidence: 50%
“…As such, the drawdown of nitrate was likely dependent on recycled iron still resident from the previous year, having been introduced as new iron with deep mixing in the winter of 2013 (Figure 6d). Mtshali et al (2019) reported that recycled iron supported seasonally extended primary production in the Southern Ocean; we suggest that this extension reached into the first warm-year growing season in the Gulf of Alaska. The NCP collapse in the second warm year suggests a loss of resilience in the system.…”
Section: 1029/2019gb006327mentioning
confidence: 50%
“…On the intraseasonal scale, we investigated whether summer storms could supply iron to support summer production above and beyond these seasonal iron supplies. Storm‐driven supplies are currently unresolved by temporal coverage of available DFe observations (Mtshali et al, ). In agreement with Fauchereau et al () and Carranza and Gille (), we found strong positive correlations between storm‐driven anomalies of the MLD with surface chlorophyll but also with primary production (Figures a and b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the "once-off" seasonal supply, there is increasing observational evidence from satellites (Carranza & Gille, 2015;Fauchereau et al, 2011;Thomalla et al, 2011) and from in situ high-resolution gliders (Mtshali et al, 2019;Swart et al, 2015) that storms could be entraining intermittent DFe supplies that could support phytoplankton production, especially in summer when DFe limitations are strongest (Boyd, 2002;Mtshali et al, 2019;Ryan-Keogh et al, 2018). Carranza and Gille (2015) found strong positive correlations between high wind speeds with enhanced surface chlorophyll in summer and concluded that local storm-driven entrainment was the dominant nutrient supply mechanism over advection by Ekman pumping.…”
Section: Introductionmentioning
confidence: 99%
“…We expect that deep winter mixing drives entrainment of higher concentrations of trace metals from depth into surface waters (Cloete et al ). Spring sees a rapid decrease in surface dFe concentration as the mixed layer shoals and both biological uptake and abiotic particle scavenging accelerates (Mtshali et al ). We expect that Fe concentrations should remain low through summer and drive species succession from microphytoplankton with rapid growth rates and high Fe demand in spring toward nanophytoplankton and picophytoplankton with lower Fe demand later in the season.…”
mentioning
confidence: 99%